The Economics of Renewable Energy and its relationship to Sustainable Development in the Sudan 2010-2020 - Suleiman, Mai Musa (Journal of Economic, Administrative and Legal Sciences, 2022)
Energy, especially renewable is considered an essential ingredient in sustaining development, since its availability and accessibility considered a very important topic worldwide. Therefore, SDG incorporated a clear goal related to sustainable energy which assures the necessity of accesablity of all to sustainable, reliable energy with reasonable cost. The research problem centred in that Sudan owns so many diversified sources for producing renewable energy (RE), but the capacity utilized from it doesn’t match the existing potentialities. The research based on central hypothesis which is that RE has a positive relationship with Sustainable development. From this central hypothesis many sub hypothesis has been set, among which is the existence of reliable relations between energy objective and the other SDGs, and between energy consumption and economic. Also, Sudan owns diversified sources of producing RE that can contribute in its development. The research relied on analytical descriptive methodology using NARDL Model and Granger causality test to rest the relationship between energy consumption and economic growth during the research period. The main research findings are that there is an integrated, bidirectional causal relationship between electricity consumption and economic growth in the Sudan in both short al long runs, with an energy sustainability index of 30% (2020) which is the lower compared to the regional Arab and African countries. The research recommended several recommendations, the importance among which were the necessities of utilizing the existing low cost electricity network with Ethiopia and Egypt to fill the current consumption gap. Also, the importance of easing investment barriers in RE for investors, specifically for solar and wind sectors for better serving the development goals in the country.